EXAMINING THE EFFECT OF HIGH SEASONALITY ON FRONTLINE EMPLOYEES: A CASE STUDY OF FIVE STARS HOTELS IN AQABA - Alananzeh, Omar Abedalla; Mahmoud, Rami Muneer; Ahmed, Mustafa N. J. (European Scientific Journal, ESJ, 2015)
In recent times, the impact of seasonality on tourism industry has been recognized. There has been a distinct lack of studies that focus on the effects of high seasonality on front-line employees (the receptionist) in hotels. Therefore, this study attempted to address the importance of the receptionist job in high seasonality and the effect of high seasonality on them. To answer the questions of the study, an instrument was used for evaluation. Also, a questionnaire was addressed to both employees and managers. T-test, ANOVA, and multiple regressions were utilized to test the hypotheses. The findings of the study revealed that the high seasonality in hotels has effects on the receptionists regarding miscommunication and bad relation with others during work hours. Therefore, this study has several recommendations for both the managers and the enterprises.